If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 2 + -1(6x + -7) Reorder the terms: 5 + 5x = 2 + -1(6x + -7) Reorder the terms: 5 + 5x = 2 + -1(-7 + 6x) 5 + 5x = 2 + (-7 * -1 + 6x * -1) 5 + 5x = 2 + (7 + -6x) Combine like terms: 2 + 7 = 9 5 + 5x = 9 + -6x Solving 5 + 5x = 9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + 5x + 6x = 9 + -6x + 6x Combine like terms: 5x + 6x = 11x 5 + 11x = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + 11x = 9 + 0 5 + 11x = 9 Add '-5' to each side of the equation. 5 + -5 + 11x = 9 + -5 Combine like terms: 5 + -5 = 0 0 + 11x = 9 + -5 11x = 9 + -5 Combine like terms: 9 + -5 = 4 11x = 4 Divide each side by '11'. x = 0.3636363636 Simplifying x = 0.3636363636
| -4(r+9)=-55 | | 4-3x-10=-8 | | -14+n=14 | | -8x+11+9x=5+x+6 | | 9x+13=2x | | 5+(-k)=3 | | 2(x+4)/3=12 | | 7x+4x-48=32-5x | | 8x+5-2x=29 | | 6(x-7)+7=6x+2 | | 2(x/3+4)=12 | | 6x-7+7=6x+2 | | -5x+605=0 | | 5x+7=2(2x+5) | | 2x+4/3=12 | | 2z+3/3+3z-4=z-2/2 | | 4(-x+3)=-2(2x-6) | | 11=5(x-4)-(x-7) | | X=4(x+3)-6 | | b-1+7b=28 | | k/10=100 | | 0.1(x+60)-0.04(x-50)=5 | | 6(6x+7)=6 | | 24-2y=8y-7 | | -6a+24= | | 5+3=-4x+47 | | 6=6/10 | | 7y+12=3y-4 | | -4/3u-6=7/3u+8 | | -(4x-4)-(3x-5)+4=-9(x-1)-(2x+7)+3 | | -x-18= | | x+5-11=-3 |